2018
DOI: 10.1016/j.actbio.2018.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and protein synthesis of esterase from Streptococcus mutans are affected by biodegradation by-product from methacrylate resin composites and adhesives

Abstract: An esterase from S. mutans UA159, SMU_118c, was shown to hydrolyze methacrylate resin-based dental monomers. Objective: To investigate the association of SMU_118c to the whole cellular hydrolytic activity of S. mutans toward polymerized resin composites, and to examine how the bacterium adapts its hydrolytic activity in response to environmental stresses triggered by the presence of a resin composites and adhesives biodegradation by-product (BBP). Materials and Methods: Biofilms of S. mutans UA159 parent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 73 publications
(108 reference statements)
0
47
0
Order By: Relevance
“…Additionally, some researchers claim that unreacted monomers and composite degradation products can promote the growth of several species of cariogenic bacteria [81,82]. S. mutans is capable of catalysing the hydrolysis of the resin matrix used in dental composites and adhesives; the bacteria increase esterase production in response to degradation products, thus accelerating the biodegradation processes [83]. The formation of a dense bacterial biofilm can also result in the ongoing destruction of resin composite because of the associated changes in surface roughness and degradation by the microorganism's esterase activities [84].…”
Section: In Vitro Ageingmentioning
confidence: 99%
“…Additionally, some researchers claim that unreacted monomers and composite degradation products can promote the growth of several species of cariogenic bacteria [81,82]. S. mutans is capable of catalysing the hydrolysis of the resin matrix used in dental composites and adhesives; the bacteria increase esterase production in response to degradation products, thus accelerating the biodegradation processes [83]. The formation of a dense bacterial biofilm can also result in the ongoing destruction of resin composite because of the associated changes in surface roughness and degradation by the microorganism's esterase activities [84].…”
Section: In Vitro Ageingmentioning
confidence: 99%
“…Nitrophenyl esters have been previously used to characterize esterases from human saliva and cariogenic dental bacteria with resin degrading properties [3,4,[6][7][8]. In the current study, human neutrophils cleaved the nitrophenyl esters and showed CE-like activity in levels relevant to intraoral degradative conditions by saliva and bacteria [3,4,6,24,28]. The data in the current study demonstrate that human neutrophils are able to significantly hydrolyze bisGMA monomers for up to 48 hours post-harvesting, corroborating the finding of previous work that has shown that CE-like activities have a high affinity for hydrolyzing this monomer [4,6].…”
Section: Esterase Ce-like Activity From Neutrophilsmentioning
confidence: 63%
“…S. mutans ’ role in biodegradation was further investigated by Huang et al [51, 61, 79]. In this work, the genome of S. mutans UA159, a clinically-relevant cariogenic strain (that had its genome mapped by Ajdic et al [80]) was searched for potential esterases.…”
Section: The Challenge Of Degradation In the Oral Cavitymentioning
confidence: 99%
“…SMU_118c showed a high degree of stability by maintaining its activity for over 20 days under both neutral and under acidic cariogenic conditions, and demonstrated a very strong ability to degrade bisGMA in its monomer form as well as in commercial composite and adhesive resins. Correspondingly, specimens incubated with S. mutans UA159 wild type released large amounts of bisHPPP and showed clear signs of surface erosion after 30 days [61]. In contrast, SMU_118c knockout (KO) strain of S. mutans UA159 lost most of its degradative activity toward polymerized composites vs. the wild type.…”
Section: The Challenge Of Degradation In the Oral Cavitymentioning
confidence: 99%
See 1 more Smart Citation